Root Length and Root Weight of Pak Choy (Brassica chinensis L.) in Wick System Hydroponics Impact of Liquid Organic Fertilizer - Nova Triani; Ahmad Zaydan Hanif; Fadila Suryandika (Future Science, 2023)
Organic farming is gaining attention worldwide because it is healthier. Pak choy plants (Brassica chinensis L.) have various benefits and are widely consumed by the public. Roots are plant organs that function in holding the plant up and absorbing water and nutrients into the plant body. Many pak choy plants are cultivated using a hydroponic system. Liquid organic fertilizer (LOF) can be a nutritional alternative for plants that are cultivated hydroponically but organically. This research aims to determine the effect of concentration and interval of application of liquid organic fertilizer on the hydroponic wick system on pak choy plants. The research was carried out from August to September 2022 at Green House Emak Farm and Hydroponic Wadungasri, Waru, Sidoarjo Regency. This research is a factorial experiment with two factors arranged in a Completely Randomized Design (CRD). The first factor is NASA liquid organic fertilizer nutrient concentration with 4 treatment levels (5, 10, 15, 20 ml/L), while the second factor is the time interval for administering liquid organic fertilizer which consists of 3 treatment levels (3, 5, and once every 7 days). Control treatment using AB mix nutrition. Each treatment was repeated 3 times and used 4 plant samples. The results of the research showed that the combination of liquid organic fertilizer treatment with a concentration of 10 ml/L and at intervals of once every 3 days had a real impact on the observation parameter of fresh root weight of 11.07 grams. The interval treatment for applying liquid organic fertilizer had a significant effect on the root length parameters of pak choy plants, namely 10.79 cm.